Crystallization and preliminary X‐ray crystallographic analysis of the curli transporter CsgG. Issue 12 (1st December 2013) - Goyal, Parveen; Van Gerven, Nani; Jonckheere, Wim; Remaut, Han
<x xml:space="preserve">Abstract</x> Gram‐negative bacteria have eight known protein secretion systems. The type‐VIII secretion system, also known as the curli biosynthesis system, is responsible for the formation of aggregative fibres known in Escherichia coli as curli. Curli are extracellular proteinaceous fibres primarily involved in bacterial biofilm formation and attachment to nonbiotic surfaces. The secretion of curli subunits depends on a dedicated lipoprotein, CsgG, which is found to form an oligomeric secretion channel in the outer membrane. A nonlipidated mutant of CsgG was expressed and crystallized in a soluble form. The crystals diffracted to 3.15 Å resolution and belong to space group P1 with a unit cell containing a predicted 16 molecules per asymmetric unit.